2022
DOI: 10.1152/ajpcell.00005.2022
|View full text |Cite
|
Sign up to set email alerts
|

Exercise mitigates the Toll of muscle atrophy: a narrative review of the effects of exercise on Toll-like receptor-4 in leukocytes and skeletal muscle

Abstract: Conditions characterized by muscle wasting such as cachexia and sarcopenia are devastating at the individual level, and they place a profound burden on public health. Evidence suggests that inflammation is likely a mechanistic contributor to the pathogenesis of these conditions. One specific molecule, lipopolysaccharide, has gained attention due to its role in initiating inflammation. Toll-like receptor-4 is the primary receptor for lipopolysaccharide and has been shown to be implicit in the downstream proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Exercise in hypoxia increased TNF-α, IL-1β, and MCP-1 in both the placebo and ibuprofen trials (main effect of time). MCP-1 is a chemokine involved in the recruitment of various leukocytes (primarily monocytes) to sites of inflammation or injury, whereas TNF-α and IL-1β are proinflammatory cytokines, which play important roles in the immune/inflammatory response to LPS through the interaction with Toll-like receptor-4 (TLR-4) (40). Thus, the increases in TNF-α and IL-1β may be explained by exercise-induced LPS translocation, enhanced TLR-4 activation enabled by elevated sCD14 presenting LPS to TLR-4, or a combination of the two (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise in hypoxia increased TNF-α, IL-1β, and MCP-1 in both the placebo and ibuprofen trials (main effect of time). MCP-1 is a chemokine involved in the recruitment of various leukocytes (primarily monocytes) to sites of inflammation or injury, whereas TNF-α and IL-1β are proinflammatory cytokines, which play important roles in the immune/inflammatory response to LPS through the interaction with Toll-like receptor-4 (TLR-4) (40). Thus, the increases in TNF-α and IL-1β may be explained by exercise-induced LPS translocation, enhanced TLR-4 activation enabled by elevated sCD14 presenting LPS to TLR-4, or a combination of the two (40).…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 is a chemokine involved in the recruitment of various leukocytes (primarily monocytes) to sites of inflammation or injury, whereas TNF-α and IL-1β are proinflammatory cytokines, which play important roles in the immune/inflammatory response to LPS through the interaction with Toll-like receptor-4 (TLR-4) (40). Thus, the increases in TNF-α and IL-1β may be explained by exercise-induced LPS translocation, enhanced TLR-4 activation enabled by elevated sCD14 presenting LPS to TLR-4, or a combination of the two (40). Interestingly, although markers of intestinal injury and microbial translocation were higher, we report lower circulating markers of inflammation in the ibuprofen trial.…”
Section: Discussionmentioning
confidence: 99%
“…Ten TLRs (TLR1‐10) are expressed in human skeletal muscle (Nishimuru & Naito, 2005; Perkins et al., 1985; Pillon & Krook, 2017). Of the 10 TLRs that exist in humans, many function in line with RAGE as a result of recognizing similar PAMPs/DAMPs, convergence on the intracellular adaptor protein (i.e., Myd88), and activation of the NFκB pathway (Ducharme et al., 2022; Federico et al., 2020; Kawai & Akira, 2010; Nielsen et al., 2017). More specifically, TLR2 and TLR4 are two of the most highly expressed TLRs in human skeletal muscle (Perkins et al., 1985; Pillon & Krook, 2017) and each has been shown to recognize PAMPs/DAMPs that are commonly shown to be elevated in insulin‐resistant individuals, such as lipoproteins, high mobility group box 1 (HMGB1), lipopolysaccharide (LPS), and AGEs (Choi et al., 2012; Tsan & Goa, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Together, cRAGE and esRAGE comprise to the total soluble (sRAGE) population and once in the circulation are suspected to function similarly as sTLRs. Several studies have shown that aerobic exercise (AE) and stimulated muscle contractions augment circulating solubilized receptor concentrations (Choi et al., 2012; Ducharme et al., 2022; Kotani et al., 2011; Legaard et al., 2022; Santilli et al., 2013). While it is difficult to conclusively determine the origin of these solubilized receptors after appearing in the circulation, many tissues have been shown to contain or produce solubilized receptors (Henrick et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring-like receptor (TLR-4) belongs to the family of TLR which, when activated in cells of the body, initiates a chain of events (Mohamed et al, 2022). Toll-like receptor-4 is the primary receptor for LPS and is involved in the proin ammatory response, and Toll-like-4 is expressed by different types of cells throughout the human body (Ducharme et al, 2022). TLR-4 can be considered an important target for the treatment of febrile seizures in FS rats (Zaniani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%